Improvements of the maintenance of special purpose devices by analog filter modernization - Radonjić, Vojkan M.; Đukić, Slobodan R.; Jovanović, Danko M.; Petrović, Saša M. (Vojnotehnički glasnik / Military Technical Courier, 2014)
This paper deals with an analysis and a comparison of the reliability of two types of special-purpose devices used in radio-relay systems. Based on the results of the analysis and the experience in top-level domains device maintenance, this paper proposes a modernization method of the existing analog radio-frequency filter with an appropriate digital filter. The proposed modernization of the technological process improves the characteristics of maintainability, increases reliability in performance while dramatically reducing the cost of equipment maintenance. Introduction All technical devices during their lifetime pass various stages, from construction, development and production, through operation and maintenance to the end of their life cycle. This paper conducted research and an analysis on the GRC 408E  special purpose device  which did not pass the phases of construction, development and production in national institutions. An optimal model of the concept of maintenance and maintenance organization of this type of device is presented in the available literature. Taking into account that, during the system lifetime, equipment modernization can be implemented, this paper deals with a comprehensive study aimed at finding the weaknesses of the device and proposes its modernization. The device modernization  by a modernizing set was modeled by an appropriate software design tool and the modernization costs were then approximated. The conducted research is based on: 1-   determining the reliability function of t the RRU-9B device and its component modules, 2-   determining the reliability function of the GRC 408E device and its component modules, 3-   analysis and mutual comparison of the reliability function of the two types of devices and their component modules, 4-   laboratory measurements, 5-   experience from the highest level of the GRC 408E equipment maintenance Conditions for the research realization The research faced a number of difficulties since there is not enough data from the exploitation of the GRC 408E special purpose device that can be used as reliability indicators. Therefore, the analysis and research directed towards the reliability function were carried out in two ways: -         for the RRU-9B device, the research was based on the patterns of failure time in the period from 2006 to 2013, -         for the GRC 408E device, the research was based on the calculated failure intensity of the integral components of individual modules. Determining the reliability function of the RRU-9B device The reliability function was determined by determining the law of distribution of work time to failure on a sample of 50 devices. Based on the data on work time to failure,  the empirical distribution function of the time to failure is determined. After that, the appropriate method is applied for an approximation of the empirical distribution with the corresponding theoretical distribution, followed by the approximation verification by appropriate testing. This paper also deals with the empirical (estimated) reliability function approximation by theoretical distributions: Weibull, exponential and normal. The testing of the obtained approximations is carried out using the following tests: Kolmogorov-Smirnov, Pearson and Romanovskogo. Approximation of the empirical distribution by the Weibull distribution Figure 2 shows the approximation of the empirical distribution by the Weibull distribution. After the completion of the testing, it is concluded that the approximation satisfies all three types of tests. Approximation of the empirical distribution by the exponential distribution Figure 3 shows the approximation of the empirical distribution by the exponential distribution. After the completion of the test, it is concluded that the approximation does not satisfy the Kolmogorov-Smirnov test, while it satisfies the Pearson and Romanovskogo tests. Approximation of the empirical distribution by the normal distribution Figure 4 shows the approximation of the empirical distribution by the normal distribution. After the completion of the testing, it is concluded that the approximation satisfies all three types of tests. Grouping the number of failures per time intervals results in losing  the accuracy of statistical measures. The commands in the MATLAB are used to calculate the cumulative probability distribution function, i.e. a function of uncertainty based on a sample of 50 devices. Based on these results, it is concluded that the Weibull distribution best approximates the empirical distribution. The Weibull distribution with corresponding parameters is is accepted and the function of reliability for the RRU-9B device has the form as in formula (1). Determining  the reliability function of the RRU-9B device modulesData on the reliability functions of the  RRU-9B components is necessary for the further analysis in order to compare these functions to the reliability functions of the components of the GRC 408E special purpose device. The calculation of the reliability function is performed by a suitable method for a small sample. Estimated values ​​of the amplifier module reliability Figure 5 shows the graphical values ​​of the reliability and unreliability functions of the amplifier module. The estimated values ​​of the reliability function are approximated by the corresponding theoretical distribution functions as follows: Weibull, exponential and normal distribution. Based on the analysis and the corresponding testing, it is concluded that only the Weibull distribution satisfies the test. Therefore, the Weibull distribution is adopted as an approximate distribution of the empirical distribution function according to formula (5). Figure 6 shows the deviation of the Weibull distribution from the empirical distribution for the case of the amplifier module. The analysis has also been appliedto other RRU-9B components and the same test results have been obtained as shown in Table 3. Determination of the reliability function of the GRC 408E special purpose  device Table 4 presents the data on the intensity of failure of particular modules as well as of  the entire GRC 408E device. The reliability function of the modules and the device is calculated based on formula (6). Figure 7 shows a comparison of the reliability functions of two devices from which it is concluded explicitely that the GRC device is more reliable in operation. A comparison of the reliability functions of modules of two devices has been carried out in a similar way  Only the RRU-9B filter module has higher values of the reliability function. These results are expected because the two filters are structurally similar, the only difference being in the GRC filter which is upgraded with stepper motors for filter control. This upgrade increased the intensity of filter module failure so the value of the reliability function is lower. The conducted analysis leads to the conclusion that if we want to increase the level of reliability of the filter modules, their construction must be modernized, which will increase the whole device reliability value. The analysis will be extended to the experience gained during the device maintenance. The experience during the maintenance of the filter module of the GRC device This section explains the most common cases of malfunctions caused by the filter module. Figure 11 shows the filter characteristics of the defective device, while Figure 12 gives the filter characteristics after corrective maintenance actions at the highest level of maintenance. Based on the experience of special-purpose device maintenance, it  can be concluded that in the future  the filter should be modernized in order to increase the reliability of the whole unit. Existing solution of the RF filter Figure 13 shows the existing solution of the analog filter. The filter control and adjustment is done by using stepper motors which obtain the data on positioning to the operating frequency from the A13 official channel module. The filter default value is 35% of the entire device value. Proposal for an RF filter modernization Figure 14 shows the block diagram of the proposed modernization of the existing analog RF filters. The modernizing set to be included instead of the filter module consists of: A/D  converter, digital filter, and D/A converter. Converters are of commercial performance and are not a subject of research. Using appropriate software tools to design digital filters led to the structure of the digital filter implemented using Xilinx's System Generator software which provides a link with Matlab and captures the amplitude characteristic. The latest generation of FPGA circuits (Xilinx's Virtex 7) is used, which allows a significant increase in the maximum sampling rate. The filter is realized on the basis of frequency masking (Frequency-response masking technique). A proposal for the implementation of digital filters is shown in Figure 16, while Figure 17 shows a comparison of the obtained amplitude characteristic of the proposed digital filter and the analog filter existing solution. Based on the available literature, the failure intensity of the modernization set has been calculated, where the value is several times lower than in the existing solutions. The modernization set  value expressed in hard currency is approximately$ 650, which is much less than the price of an analog filter. The limiting factor for the implementation of the proposed modernization is creating future hardware conditions that will allow the operation of a digital filter at frequencies at which the given special-purpose device operates. Having in mind the development in the technology of VLSI (VeryLargeScaleIntegration) components, it is expected that the new generation components in VLSI technology will soon be applied at  higher frequencies. Conclusion This paper carried out a comprehensive analysis and a comparison of the reliability characteristics of the existing equipment and its component modules with a newly acquired special-purpose device. Based on the analysis and the experience of maintenance, it is concluded that the modernization of the RF filter module is useful in order to improve the reliability and maintenance. In this sense, a modernization of the existing analog RF filter is proposed. The modernization is modeled by appropriate software tools for digital filter design, and the obtained results justify the conducted research. Based on the results of the digital filter modeling and the examination of the possibilities of its application in the GRC 408E device, it can be concluded: -        failure intensity of the modernization set is lower than the current value of the failure intensity of the A19 module which is , -        transition zone is narrow (sharp amplitude characteristic), resulting in better frequency resolution, -        cost of the modernization set is much lower than the cost of the analog RF filter, -        weight and dimensions are much smaller which makes the device easier to operate and transport, -        maintenance is possible in terms of the aggregate replacement of the modernization set by a new one or by transferring it from another device, which is not possible in the current structure of the filter without additional calibration and adjustment which must be carried out in the laboratory, -        aggregate replacement of the modernization set enables corrective maintenance to be implemented at the intermediate level of maintenance, -        corrective maintenance is simple and involves the replacement of a component, FPGA or DSP processors, -        corrective maintenance period is much shorter than in the case of mechanical analog filters with resonant cavities, resulting in  the improved characteristics of maintainability, -        a reliable diagnostics of the modernization set accuracy is provided  at all levels of maintenance, -        digital filter operation control through the central processing unit is easy and reliable, and the filter response to frequency change is instantaneous. The conducted research contributes to the maintenance of this type of devices, since, on the basis of the obtained results, it is concluded that in the future it will be possible to substitute existing analog filters with new digital ones and that the proposed modernization is justified from all aspects of maintenance.
Keywords: reliability; maintenance; modernization; Filters